Rancangan Sistem Perlindungan Korban Tindak Pidana Kekerasan Berbasis Elektronik Melalui Aplikasi Viktima bagi Warga Kampus di Universitas Galuh - Zulkipli Lubis, Fahmi; Yudi Permana, Nana; Amin Effendy, Muhammad; Ramdani, Fitriyana; Susilawati, Siska (Jurnal Accounting Information System (AIMS), 2025)
Violence on campus remains a serious problem that threatens the security and well-being of the academic community. The lack of a safe, fast, and reliable reporting mechanism often causes many victims to choose silence, thereby neglecting their right to protection. This study aims to design an electronic-based victim protection system for victims of violent crimes through the Viktima application for campus residents at Galuh University as an innovative solution in preventing and handling cases of violence. The research method used the Rapid Application Development (RAD) approach, which includes the stages of planning, workshop design, construction, and implementation. Data were obtained through interviews, observations, and questionnaires with lecturers, students, and the PPKPT Task Force at Galuh University. A needs analysis revealed that users desired anonymous reporting features, psychological support, and notifications on case progress. The application was then developed with an emphasis on data confidentiality, ease of access, and integration of support services. The trial results showed that the Viktima Electronic application was able to increase the effectiveness of reporting and victims' confidence in reporting cases of violence. The system's feasibility level based on the System Usability Scale (SUS) reached a score of 81.25, which is categorized as very good. In addition, this application supports the implementation of Permendikbudristek No. 55 of 2024, which requires universities to provide victim protection mechanisms. This study concludes that the use of information technology through the Viktima application is effective in strengthening the protection system for victims of violence on campus. The application has the potential to become a model that can be replicated at other universities in an effort to create a safe, inclusive, and violence-free academic environment.